2020
DOI: 10.1007/s43151-020-00004-6
|View full text |Cite
|
Sign up to set email alerts
|

Regime Change: Education to Work Transitions in England, 1980s–2020s

Abstract: This paper argues the case for viewing a country's transition regime as a totality in which different career steps and routes assign significance and value to one another. Following the destruction of major sections of Britain's transition regime in the 1970s and 1980s, the paper explains how the regime has subsequently been reconstructed following the 1988 Education Reform Act, replacing the vocational education and training schemes of the 1980s with government-supported apprenticeships, almost uninterrupted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…These issues are addressed using the transition regime concept. A regime is a system of inter-connected parts that assign value and meaning to each other (see Raffe, 2014;Roberts, 2020;Walter, 2006). The "parts" are types and levels of education, training, and subsequent employment.…”
Section: Methodsmentioning
confidence: 99%
“…These issues are addressed using the transition regime concept. A regime is a system of inter-connected parts that assign value and meaning to each other (see Raffe, 2014;Roberts, 2020;Walter, 2006). The "parts" are types and levels of education, training, and subsequent employment.…”
Section: Methodsmentioning
confidence: 99%
“…Co-researchers from different countries have found themselves encountering educational institutions and qualifications not only with unfamiliar titles but playing roles in young people's transitions with no direct counterparts in other researchers' home countries. This was the context in which researchers began to conceptualise 'transition regimes' in which each part acquired significance only from its relationship with other parts of the regime (discussed fully in Roberts, 2020) [3]. Each step that a young person could take acquired value and significance from the typically preceding and subsequent positions.…”
Section: Transition Regimesmentioning
confidence: 99%
“…However, for others it has become a career-long position as less-qualified beginners have found that former routes upwards have been broken [71][72][73][74][75]. The least qualified school-leavers have become distinctly tail-end, around 20 percent of the age groups who leave education without any qualifications that will assist in their searches for work [76]. This 'tail' is drawn mainly from Britain's least advantaged, poorest families.…”
Section: Class In the New Millenniummentioning
confidence: 99%